DAMPAK EKSPOR UBI KAYU INDONESIA KE MALAYSIA (2009-2014) - Saaduddin, Awal Fitrah; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research discuss about the impact of export Indonesia’s cassava to Malaysia (2009-2014). The aim of this research is it know what export cassava’s impact to the economic and political sectors in Indonesia. Cassava was choosen as a research subject because as one of the best commodities in national commodities. Not only in a good climate, good temperature, good human and natural resources. But also easy in the planting, growing, and having ability to be food stufle and industrial raw is the reason this research appointment. Based on author would like to see what is the impact of economic and political term. From cassava’s export after that cooperation process for Indonesia which is able to be a reference for other.This also explain how the Indonesia government’s efforts in building these commodities and makes this commodity is able to full fill domestic demand and take it off as an export commodity based a second cooperation between Indonesia and Malaysia regarding of foodcrops cooperation. In the other case, demands to the Indonesia government in has role foe that success of this cassava’s commodity export to Malaysia is needed all efforts both in pro-farmers, regulation, policy, strategy, innovation, and good accomodation like of export equipment, and capital. The government should be able to accommodate every farmer’s need, which is the success of a country for farmers is the creation of an agribusiness based on national and international agricultural.Keywords: impact, export, cassava, national commodity, Indonesia, Malaysia.